The Effect of Corporate Taxes on Investment and Entrepreneurship - Djankov, Simeon; Ganser, Tim; McLiesh, Caralee; Ramalho, Rita; Shleifer, Andrei (2012)
We present new data on effective corporate income tax rates in 85 countries in 2004. The data come from a survey, conducted jointly with PricewaterhouseCoopers, of all taxes imposed on "the same" standardized mid-size domestic firm. In a cross-section of countries, our estimates of the effective corporate tax rate have a large adverse impact on aggregate investment, FDI, and entrepreneurial activity. Corporate tax rates are correlated with investment in manufacturing but not services, as well as with the size of the informal economy. The results are robust to the inclusion of many controls.